What is the truth about DSGE models? Testing by indirect inference - David Meenagh; Patrick Minford; Michael R. Wickens; Yongdeng Xu (Cardiff University, Cardiff Business School, 2016)
This paper addresses the growing gulf between traditional macroeconometrics and the increasingly dominant preference among macroeconomists to use DSGE models and to estimate them using Bayesian estimation with strong priors but not to test them as they are likely to fail conventional statistical tests. This is in conflict with the high scientific ideals with which DSGE models were first invested in their aim of finding true models of the macroeconomy. As macro models are in reality only approximate representations of the economy, we argue that a pseudo-true inferential framework should be used to provide a measure of the robustness of DSGE models.
Keywords: C12; C32; C52; E1; 330; Pseudo-true inference; DSGE models; Indirect Inference; Wald tests; Likelihood Ratio tests; robustness